PERFORMANCE ANALYSIS OF ELECTRIC VEHICLE CONVERSION AT CENTER OF GRAVITY MEASUREMENT - F. Zainuri; D. A. Sumarsono; Mohammad Adhitya; I. Wahyudi; I. Choiri; A. Azis; G. Fauzan; M. Triananda; F. Arrafi; F. A. Falah (Jurnal Teknologika, 2020)
In this study, the conversion is done by changing conventional gasoline-powered vehicles with electricity. Replacement is done by removing the drive engine and replacing it with a drive motor that is automatically added to the battery as an energy source. Laying the existing components affects the center of grafity where all car weights are centered in one meeting point. The car that we usually see on the road has a lot of heavy components, such as engine blocks, pistons, batteries, gearboxes, axles, transfer cases and heavy components scattered throughout the car, so naturally there is a "meeting point" where all the heavy components it rests when installed. "Intersection" is the center of weight of the car. From the results of measurements and calculations, the value obtained from the change in weight of conventional vehicles to electric vehicles is quite significant around 300 kg, this is dominated by the addition of motor components in front and a total battery of 300 kg. Significant changes related to changes in center of grafity that result in a center of gravity that has been measured and calculated in good condition because the value has changed from 38.94% (front to back) to 54.50% and is in the middle of the car because the lower, the middle, the more nice. Likewise, a change of 50.34% to 50.95% (from left to right) so that the lower the center of gravity of the car, the effect will be felt when the car is bent at a bend or maneuver. Cars with low center of gravity will be more stable and have less symptoms of dizziness, so it feels more easily controlled. Heavy displacement when turning and braking is also increasingly minimal and easy to read, so the car is very easily controlled by the rider.This study and trial aims to determine the pattern of power consumption on the Kendaraan konversi and the reliability of the system. Thus the data obtained for further study related to the way of recharging the battery and improvement kendaraan konversi work system.